Rank a run: Creating the future of runs - together - Sonderup, L.; Damsbo, J.; Veggerby, J. (New Studies in Athletics, 2015)
The participant experience that road races seek to deliver often reflects the racer director's own experience as a runner and his/her personal preferences. It is rare that such product quality decisions are made on the basis of evidence about what the mass of runners actually expect In 2012 the authors launched Rank A Run, a user-friendly online survey tool created to enable race organisers to collect data on participants and thereby gain understanding of their expectations and other thoughts/feelings about the event. It has been tested by more than 60 events in Denmark and the intention is to make it more widely available to organisers globally. This case study describes the development process, how the tool is used and the survey itself before summarising the value propositions for organisers, runners and partners. The authors conclude by recommending that national athletics federations and European Athletics to consider how the concept of Rank A Run might be used to enhance their positions in the national and European running markets and their ability to strengthen running events and their organisers.